Survey study for transfer of cadmium and chromium in soil and wheat (Triticum aestivum L.), grown on contaminated soils - Virk, Fahad Iftikhar; Muhammad Sarfraz, Muhammad Qaisar Nawaz; Bibi, Sadia; Waqas, Muhammad (Journal of Scientific Agriculture, 2023)
This study was conducted to evaluate the contamination and accumulation of heavy metals such as Cadmium (Cd) and Chromium (Cr) in soil and plant grown in contaminated soil. Orchard and relative non-orchard fields were chosen to carry out this study. For total and available metals, soil samples were collected equally from 24 different points of orchard and non-orchard field and were extracted with Mehlich-3 extracting solutions and aqua-regia. Wheat crops from orchard and non-orchard fields were analysed and collected with aqua regia for heavy metal contents. Irrigation water samples were also collected from fresh water irrigation canal (Lower Chenab) for analysis. Results indicated that average metal concentrations in soils of both orchard and non-orchard fields were Cadmium (Cd) 2.36 and 2.49 mg kg-1 and Chromium (Cr) 58.15 and 53.51 mg kg-1 respectively. Contribution of risk from Cd and Cr were significant in wheat (seeds) of orchard. In orchard field, the risk contribution from Cd and Cr were significant in crops seeds. The considerable load of toxic metals in fields revealed the anthropogenic source of pollution. Therefore, it is emphasize that the need of heavy metals monitoring in crops and soils is necessary.